The Effect of Dhikr Therapy Combined with Warm Water Foot Soak Therapy on Sleep Quality in Elderly People with Hypertension in the Pekauman Community Health Center Working Area, Banjarmasin - Zulfirmansyah, Rizqilla Az-zahra; Wijaksono, M. Arief; Syahlani, Ahmad (PROMOTOR, 2025)
Hypertension is a high blood pressure disease that commonly occurs in the elderly. Elderly people with hypertension may experience a decline in sleep quality, which can worsen their health condition. A combination of dhikr therapy and soaking feet in warm water is needed as an intervention to improve sleep quality in the elderly. This study aims to analyze the effect of dhikr therapy combined with warm water foot soak therapy on the sleep quality of elderly people with hypertension in the working area of Pekauman Health Center, Banjarmasin. The study is a pre-experimental research with a one-group pretest-posttest design involving 15 elderly people with hypertension. The intervention was carried out by soaking the respondents’ feet in water at a temperature of 30-45℃ while performing dhikr for 15-20 minutes in the morning and evening for one week. The hypothesis was analyzed using the Wilcoxon test. Based on the research results, the majority of respondents were aged ≥60 years (80%), female (53.3%), elementary school graduates (86.6%), unemployed (73.3%), had hypertension for ≥10 years (86.7%), had poor sleep quality before therapy (93.3%), and had good sleep quality after therapy (93.3%). The p-value = 0.000, indicating that Ha is accepted, or there is an effect of dhikr therapy combined with warm water foot soak therapy on the sleep quality of the elderly. The application of the combination of dhikr therapy and warm water foot soak can improve the sleep quality of elderly people with hypertension.